2017
DOI: 10.1002/2016jc012665
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorus Budgets in the Northwestern Mediterranean Deep Convection Region

Abstract: The aim of this study is to understand the biogeochemical cycles of the northwestern Mediterranean Sea (NW Med), where a recurrent spring bloom related to dense water formation occurs. We used a coupled physical‐biogeochemical model at high resolution to simulate realistic 1 year period and analyze the nitrogen (N) and phosphorus (P) cycles. First, the model was evaluated using cruises carried out in winter, spring, and summer and a Bio‐Argo float deployed in spring. Then, the annual cycle of meteorological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 85 publications
5
48
1
Order By: Relevance
“…Regarding the vertical distribution of chlorophyll in convection regions, Kessouri et al () found a good agreement between model results and DeWEx cruise observations. Moreover, the time evolution of the vertical distribution of phytoplankton in the Stratified (southern) region is consistent with climatological observations reported by Lavigne et al (): the model correctly reproduces the formation of a deep chlorophyll maximum (DCM) after the winter mixing period and its deepening between 50 and 80 m in summer (presented in section 4.2).…”
Section: Model Evaluationsupporting
confidence: 92%
See 4 more Smart Citations
“…Regarding the vertical distribution of chlorophyll in convection regions, Kessouri et al () found a good agreement between model results and DeWEx cruise observations. Moreover, the time evolution of the vertical distribution of phytoplankton in the Stratified (southern) region is consistent with climatological observations reported by Lavigne et al (): the model correctly reproduces the formation of a deep chlorophyll maximum (DCM) after the winter mixing period and its deepening between 50 and 80 m in summer (presented in section 4.2).…”
Section: Model Evaluationsupporting
confidence: 92%
“…A detailed validation of the coupled hydrodynamic and biogeochemical models over the study period is described in Estournel et al () and Kessouri et al (), respectively. Estournel et al () conducted several comparisons with observations, such as the spatial distribution of water column stratification in winter at the scale of the northwestern subbasin (their Figure ) or time series of the potential temperature profile in the center of the Gulf of Lions (their Figure 11).…”
Section: Model Evaluationsupporting
confidence: 88%
See 3 more Smart Citations